Training Workshop on Research Proposal Writing for Faculty Members: Assessment of the Feedback of the Participants - Piryani, Rano Mal; Zeba, Nudrat; Memon, Farah Naz (Universitas Pendidikan Ganesha, 2023)
Proposal writing training enriches lecturers' capacity in conducting research. The purpose of this study was to assess direct feedback (reactions) from faculty members participating in a research proposal writing training workshop. This was a cross-sectional study conducted through a self-administered questionnaire. The data was analyzed for central tendency. Pre-questionnaire data were retro skewed, so the Wilcoxon Signed Rank Test was used for median comparisons. Open question data were checked manually. The results of this study found a ranking of training workshop attributes, namely usefulness (8.71 ± 1.23), content (8.86 ± 1.15), relevance (8.90 ± 1.18) and facilitation (9.09 ± 1.15). .09) was also quite prominent and overall (9.05±.97). Participants' confidence levels increased significantly (<0.001) on six relevant cognitive skills items; conducting research (before Median-2, IQ-1, after Median-3, IQ-0); conducting a systemic review (before Median-2, IQ-1, after Median-3, IQ-1), choosing a research design (before Median-2, IQ-2, after Median-3, IQ-0), applying basic biostatistics ( before Median-2, IQ-1, after Median-3, IQ-0), academic writing (before Median-2, IQ-1, after Median-3, IQ-0) and research proposal writing (before Median-2, IQ-1, after Median-3, IQ-0). Overall the feedback from the participants was positive and excellent and their confidence levels increased significantly on the cognitive skills assessment.